Reframing Cyber Security for the Next Generation of Digital Activists (Journal of The Colloquium for Information Systems Security Education, 2025)
This paper presents a novel short course on cyber security designed for secondary school students in the UK. Our approach uniquely frames cyber security within the context of social activism and change-making, aiming to broaden participation and break down entry barriers in the field. The course contextualizes standard cyber security concepts such as information management, privacy, threat modeling, and cryptography within scenarios relevant to young activists.We developed comprehensive lesson plans, interactive activities, and tools like “Change Cards” to facilitate engagement. The course was tested in two educational settings, leading to insights about content delivery and student engagement. Key outcomes include a teacher’s guide and professionally designed resources that have been downloaded by over 1,000 teachers worldwide.Feedback from students and teachers has been overwhelmingly positive, highlighting the course’s relevance to daily life and its effectiveness in improving understanding of security concepts. This project contributes to the field by offering an innovative approach to cyber security education that resonates with young people’s desire for social change, potentially fostering a new generation of diverse cyber security advocates and professionals.
Keywords: Cyber Security; Diversity; Social Activism